Pengembangan Model Pengasuhan Keluarga Dalam Upaya Meningkatkan Kecerdasan Emosi Dan Kemandirian Anak-Remaja Di Kabupaten Karangasem Dan Kota Denpasar - Ni Luh Putu Yunianti Suntari Cakera; I Ketut Labir (JURNAL INFO KESEHATAN, 2017)
At the present time, it is found that there are fundamental changes in almost all families. Many reported cases found discriminating women and children. In discussing children, there are many violations to the safeguard of children. And it happened in their families. Problems occur due to many factors, among others, the increasing role of older people in society, ignorance of the family in performing care for children in the current circumstances. Parents need guidance and direction in helping their children to grow and develop. This study aims to find a simple guide to help parents exercising their role optimally in order to protect children and help them to grow in intelligence and independence. A provision needed by children to face their future. Based on the above background, it can be formulated research problem which is "Do the Family Care is an effort to develop intelligence and independence of children-adolescents in Karangasem Regency and Denpasar City." The purpose of this study is to obtain a simple guidance to family care models in an effort to develop intelligence and independence of children-adolescents in Karangasem Regency and Denpasar City. The research design was quasi-experiment, with pre-post test design. It was done by Paired test and independent t-test. The obtained results with a Paired test, treatment group at STT Dharma Yowana, of Denpasar, it was found that there are significant differences in the variables of emotional intelligence (p = 0.000) and independence (p = 0.000). The treatment group at STT Dharma Bhakti, of Karangasem, showed that no significant difference in emotional intelligence variables (p = 0.010) and independence (p = 0.007). The t-test on independent variables differentiates the treatment groups in both places. After assisting the family, it did not show significant differences in emotional intelligence (p = 0.706). It is also on the independent variable, with p = 0.113, showed that no significant difference. These results show that emotional intelligence and independence of teenagers are more affected by family or parental care, compared to the neighborhood. The expected benefits families can apply the model of appropriate care for children, adolescents to cultivate intelligence and independence children-teenage. Results of research can be a concept of development materials of appropriate care model for children-adolescents to cultivate intelligence and independence of children-adolescents.